2019
DOI: 10.1016/j.jtcvs.2019.01.075
|View full text |Cite
|
Sign up to set email alerts
|

A brain natriuretic peptide-based prediction model for atrial fibrillation after thoracic surgery: Development and internal validation

Abstract: Objective-Postoperative atrial fibrillation (POAF) is common after anatomic thoracic surgery. Elevated preoperative brain natriuretic peptide (BNP) level is strongly associated with risk of POAF. We describe the development and internal validation of a clinical prediction model for POAF that includes BNP and other clinical factors. Methods-Clinical and preoperative BNP data were collected for 635 patients in sinus rhythm before anatomic lung (n=540) or esophageal (n=95) resection. The primary outcome was new o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…Consequent to their findings, Amar and colleagues 6 have suggested that all patients undergoing preoperative evaluation for noncardiac thoracic surgery ought to have BNP measured and their risk of atrial fibrillation estimated from the nomogram. Moreover, Amar and colleagues 6 have implicated that patients at higher calculated risk for atrial fibrillation development should be considered for potential antiarrhythmic prophylaxis, on the basis of previously published guidelines and studies.…”
Section: Mara B Antonoff MDmentioning
confidence: 97%
See 3 more Smart Citations
“…Consequent to their findings, Amar and colleagues 6 have suggested that all patients undergoing preoperative evaluation for noncardiac thoracic surgery ought to have BNP measured and their risk of atrial fibrillation estimated from the nomogram. Moreover, Amar and colleagues 6 have implicated that patients at higher calculated risk for atrial fibrillation development should be considered for potential antiarrhythmic prophylaxis, on the basis of previously published guidelines and studies.…”
Section: Mara B Antonoff MDmentioning
confidence: 97%
“…Consequent to their findings, Amar and colleagues 6 have suggested that all patients undergoing preoperative evaluation for noncardiac thoracic surgery ought to have BNP measured and their risk of atrial fibrillation estimated from the nomogram. Moreover, Amar and colleagues 6 have implicated that patients at higher calculated risk for atrial fibrillation development should be considered for potential antiarrhythmic prophylaxis, on the basis of previously published guidelines and studies. 2,7 Certainly, efforts to prevent atrial fibrillation in high-risk individuals may be beneficial to our patients, potentially avoiding negative adverse events related to the arrhythmia as well as the typical prolongation of hospital stay that tends to accompany its development.…”
Section: Mara B Antonoff MDmentioning
confidence: 97%
See 2 more Smart Citations
“…Unfortunately, not all thoracic surgery units around the world share the same abundant resources as those that were available to the patients who contributed to this study by Amar and colleagues. 2 Continuous cardiac monitoring for 48 to 72 hours after routine operations, such as anatomic lung and esophageal operations, although potentially preferable is not universally feasible. In fact, enhanced recovery pathways and minimal access surgery programs routinely lead to patient discharge within 24 to 48 hours from surgery.…”
mentioning
confidence: 99%